PENGAWETAN TIGA JENIS KAYU UNTUK BARANG KERAJINAN MEMAKAI DUA JENIS BAHAN PENGAWET BOR SECARA RENDAMAN DINGIN - Sasa Abdurrohim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Three Wood species, i.e. tusam (Pinus merkusii Junh. et De Vr.), karet (Hevea brasiliensis Muell. Arg.) and jeungjing paraserianthes falcataria (L.) Nielsen) were treated with two bor preservatives using cold soaking method. The two preservatives used were borax at 5 % level and the mixture of borax and boric acid at 10 % level. The soaking periods were 1, 3, 5 and 7 days. Forty samples of the size 5 x 5 x 50 cm were used for each species and each treatment in thisn experiment. The avemge moisture content of the samples for each species were 29 .9 %, 31. 9% and 30.3% respectively.The results showed that two species, i.e. tusam and karet achieved the minimum standard on preservative retention and pentatiue. The required minimum retention for borex preservative is 8. 7 kg/m3, whereas for the mixture of borax and boric acid is 8.4 kg/m3. The required minimum penetration for both preservatives is 10 mm.The .study recommended that tusam should be treated in 5 days using borax preservative or 1 day using the mixture of borax and boric, both with cold soaking method. The treatment for karet was recommended to use the mixture of borax and boric acid within 3 days.